Aqueous compatible boron nitride nanosheets for high-performance hydrogels. Issue 7 (3rd February 2016) - Hu, Xiaozhen; Liu, Jiahui; He, Qiuju; Meng, Yuan; Cao, Liu; Sun, Ya-Ping; Chen, Jijie; Lu, Fushen
Abstract : Aqueous dispersible boron nitride nanosheets were produced and used to fabricate nanocomposite hydrogels with high water retentivity and flexibility. Abstract : Hexagonal boron nitride nanosheets (BNNSs) possess ultimate thermal and chemical stabilities and mechanical strengths. However, the unmodified BNNSs are hydrophobic and insoluble in water, which hinders their use in many technological areas requiring aqueous compatibility. In this work, h-BN was treated with molten citric acid to produce aqueous dispersible boron nitride sheets (ca-BNNSs). The resultant ca-BNNSs were used to fabricate ca-BNNS/polyacrylamide ( i.e., BNNS2.5 /PAAm) nanocomposite hydrogels, targeting high water retentivity and flexibility. The BNNS2.5 /PAAm hydrogel (initially swollen in water) largely remained swollen (water content ∼94 wt%) even after one-year storage under ambient conditions. Importantly, the swollen BNNS2.5 /PAAm hydrogel (water content ∼95 wt%) was highly flexible. Its elongation and compressive strength exceeded 10 000% and 8 MPa at 97% strain, respectively. Moreover, the aforementioned hydrogel recovered upon the removal of compression force, without obvious damage. The substantially improved water retentivity and flexibility revealed that BNNSs can serve as a promising new platform in the development of high-performance hydrogels.